Rare case of lateral dislocation of the elbow without distinct radiological signs - Maleki, Arash; Qoreishi, Mohamad; Shakeri Jousheghan, Saman; Tajik, Katayoon; Gholami Manzari, Amirhossein (Journal of Contemporary Medical Sciences, 2022)
While the elbow joint dislocation is one of the most common dislocations, lateral dislocation of elbow is so rare. In this study, we described a 65-year-old woman with lateral elbow dislocation referred to Akhtar Hospital. With full range of motion in supination, pronation, and extension, as well as 60º flexion, the most important finding with this case was that the radiographic findings could not help surgeon to diagnose the lateral dislocation. Therefore, CT-scan was performed. After confirmation, closed reduction was done via a standard maneuver. The patient was followed up for 2 weeks and physiotherapy was ordered. According to this case, when there was an elbow trauma with unusual radiograph without any specific finding to confirm the lateral dislocation, it is recommended to perform CT-scan. The closed reduction and following physiotherapy also are essential for management of this condition.